ANALISIS VARIABEL-VARIABEL YANG MEMENGARUHI PERTUMBUHAN INKLUSIF DALAM MENDUKUNG PENCAPAIAN PRIORITAS PEMBANGUNAN SUMATERA SELATAN - Achmad Choirul Huda; Rahani, Rini (Jurnal Litbang Sukowati : Media Penelitian dan Pengembangan, 2025)
Inclusive growth is crucial for ensuring that economic growth is followed by poverty, inequality, and unemployment reduction. Despite experiencing high economic growth, South Sumatra still faces poverty, inequality, and employment. Therefore, the government has prioritized achieving inclusive growth as the first goal of the Regional Medium-Term Development Plan (RPJMD). This research aimed to assess the inclusive growth of cities in South Sumatra using an index developed by Ramos, Ranieri, and Lammens. Panel data regression was used to analyze the variables influencing the inclusive growth index in alignment with the strategies and policies of the RPJMD. The data used in this study was compiled from Badan Pusat Statistik, Bank Indonesia, and Kemendikbudristek. The results indicated that growth inclusiveness fluctuated from 2018 through 2022. The industry productivity, the ratio of hospitals and health centres to the total population, the ratio of the number of schools to the school-age population, and the percentage of the population with internet access had a significant effect on the inclusive growth index in South Sumatra. The government need to focus on developing leading sectors and improving access to healthcare and education to achieve inclusive growth.